On the contribution of D.I. Zaitsev to the Theory of Infinite Groups - Kirichenko, V.V.; Kurdachenko, L.A.; Otal, J.; Subbotin, I.Ya. (Algebra and Discrete Mathematics, 2012)
We survey the most outstanding contributions due to D.I. Zaitsev in the Theory of Infinite Groups.